EFFECT OF COOLING-MEDIUM INDUCED INITIAL STRUCTURE BEFORE INTERCRITICAL ANNEALING ON THE MICROSTRUCTURE AND MECHANICAL PROPERTIES OF LOW ALLOY DUAL-PHASE STEEL - Romijarso, Toni Bambang; Rohmah, Miftakhur; Ariati, Myrna; Mabruri, Efendi; Siradj, Eddy Sumarno (National Research and Innovation Agency (BRIN), 2023)
The present research focused on determining the effect of cooling-medium-induced initial structure before the intercritical annealing induced dual-phase structure in the low alloy steel. Low carbon steel, which consists of containing 0.09 wt.% C was heated at 920 °C for 30 minutes to austenitization and then cooled in various media to provide the different initial structures before the IA (intercritical annealing) process. After austenization, the cooling process in the furnace and open-air provided a ferrite-pearlite phase, while the cooling process in water generated full martensite as the initial structure. Afterwards, the sample was intercritical-annealed at 750 °C (temperature between Ac1 and Ac3 lines or intercritical zone) for 10 minutes and then quenched in water. The water quenching after the austenitizing process improved the mechanical strength of steel (919 MPa), compared to the as-received state (519 MPa) due to martensite formation. As the cooling rate increased after the austenitizing process, the tensile strength increased and the elongation decreased. The different structures before intercritical annealing affected the martensite volume fraction and further correlated with improving mechanical properties. The ferrite and pearlite, as the initial structure before the IA process, provide a smaller fraction of martensite (18.36 vol.% for furnace cooling and 27.85 vol.% for open-air cooling). In contrast, the full martensite as the initial structure before IA generates a higher fraction of martensite (39.25 vol.%). The tensile strengths obtained were 512, 516, and 541 MPa with elongations of 29.8%, 30.1% and 32.6% for cooling furnace, open air and water, respectively. The strain-hardening behavior during the intercritical annealing is not affected by the initial process of the structure.